2015
DOI: 10.1590/0103-8478cr20140407
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to antibiotic growth promoters for weanling pigs

Abstract: An experiment was conducted to evaluate the addition of sodium butyrate, plant extracts and nucleotides on weanling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In addition to major changes in the microbiota, the main concern with the extensive use of antibiotics is the emergence of antimicrobial resistance, which has already been extensively demonstrated [ 27 , 28 ]. For these reasons, the development of novel non-antibiotic strategies to prevent infection in food-producing animals, subsequently increasing animal productivity, has been a topic of intense research in the swine industry [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to major changes in the microbiota, the main concern with the extensive use of antibiotics is the emergence of antimicrobial resistance, which has already been extensively demonstrated [ 27 , 28 ]. For these reasons, the development of novel non-antibiotic strategies to prevent infection in food-producing animals, subsequently increasing animal productivity, has been a topic of intense research in the swine industry [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRAESEL et al (2011), SOUSA et al (2013), and SANTANA et al (2015 evaluated the albicans --------------------------------------------------------------------------------Peel--------------------------------------------------------------------------------10% 3.33 ± 0.33 0.17 ± 0.17 a 0.17 ± 0.17 a 0.17 ± 0.17 20% 3.17 ± 0.31 1.50 ± 0.22 0.67 ± 0.21 0.17 ± 0.17 30% 2.67 ± 0.21 3.00 ± 0.37 b 1.17 ± 0.17 b 0.17 ± 0. 17 --------------------------------------------------------------------------------Pulp--------------------------------------------------------------------------------10% 4.00 ± 0.45 0.17 ± 0.17 1.17 ± 0.17 0.17 ± 0.17 a 20%…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In weaned piglets, most of the studies (12) showed that dietary colistin supplementation at 12 to 200 mg/kg feed had positive growth-promoting effects in piglets (Guerra et al (2007), 12 mg colistin sulfate/kg feed; Mazutti et al (2016), 20 mg colistin/kg feed; Yang et al (2012) and Yu et al (2017), 20 mg colistin sulfate/kg feed; Cui et al ( 2019), 40 mg colistin sulfate/kg feed; Sbardella et al (2016) and Silva-J unior et al (2020), 40 mg colistin/kg feed; Wan et al (2015), 60 mg colistin sulfate/kg feed; Cao et al (2019), 100 mg colistin sulfate/kg feed; Kong et al (2007), Liu et al (2016) and Yin et al (2009), 200 mg colistin/kg feed). Only in two studies no growth-promoting effects of colistin in piglets were observed when administered in the diet (Santana et al (2015), 40 mg colistin sulfate/kg feed; Conde et al (2001), 150 mg colistin/kg feed). When administered at 2,000 mg colistin sulfate/kg feed, colistin showed negative effects in growth in weaned piglets (Furbeyre et al, 2017).…”
Section: Pigsmentioning
confidence: 95%
“…In the study of Santana et al. ( 2015 ), a total of 90 piglets (unspecified breed/genotype; 21‐day‐old, BW 6.35 kg) were distributed in 30 pens in groups of three animals and allocated to five dietary treatments. Two basal diets (21–35 days and 35–56 days) were either not supplemented or supplemented with different treatments.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation